1999
DOI: 10.1557/proc-606-187
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Crack-Free BaTiO3 and Pb(Zr,Ti)O3 Films Over 1 μm Thick Via Single-Step Dip-Coating

Abstract: BaTiO3 and PZT films were prepared by single-step dip-coating from alkoxide-acetate solutions containing polyvinylpyrrolidone (PVP). Crack-free BaTiO3 and PZT films over 1 μm in thickness were obtained via single-step deposition. Stepwise heating of the gel films was found to improve densification of BaTiO3 films, reducing the thickness and increasing the optical transmittance, which was not, however, the case with PZT films, where the stepwise heating rather induced crack formation, leading to degraded transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…In summarizing the effect of the heat-treatment conditions, the stepwise heating, which is effective in densifying the BaTiO 3 films without forming cracks, 8 does not work for the PZT films. The crystallization of Pb 3 (CO 3 ) 2 (OH) 2 and the tendency of the films to undergo phase separation or PVP segregation at low temperatures is the possible cause; the former and latter hinder the plastic deformation in films, and the latter increases the porosity of the films.…”
Section: (4) Evolution Of Microstructurementioning
confidence: 99%
See 2 more Smart Citations
“…In summarizing the effect of the heat-treatment conditions, the stepwise heating, which is effective in densifying the BaTiO 3 films without forming cracks, 8 does not work for the PZT films. The crystallization of Pb 3 (CO 3 ) 2 (OH) 2 and the tendency of the films to undergo phase separation or PVP segregation at low temperatures is the possible cause; the former and latter hinder the plastic deformation in films, and the latter increases the porosity of the films.…”
Section: (4) Evolution Of Microstructurementioning
confidence: 99%
“…4 The present authors previously demonstrated that polyvinylpyrrolidone (PVP) incorporated in coating solutions increased the critical thickness-i.e., the maximum thickness achievable without crack formation via nonrepetitive deposition-and could lead to formation of crack-free ceramic coatings Ͼ1 m in thickness for BaTiO 3 , PZT, and Fe 2 O 3 films. [5][6][7][8][9][10] The effect of the PVP content in solutions on critical thickness also had been studied for BaTiO 3 films and Fe 2 O 3 films derived from Ba(CH 3 COO) 2 -Ti(i-OC 3 H 7 ) 4 and Fe(NO 3 ) 3 solutions, respectively, where the maximum critical thickness was at PVP/Ti(i-OC 3 H 7 ) 4 and PVP/Fe(NO 3 ) 3 mole ratios of ϳ0. 5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors recently proposed that poly(vinylpyrrolidone) (PVP) would be an effective agent for increasing the critical thickness. [1][2][3][4][5][6] Crack-free BaTiO 3 and PZT films Ͼ1 m in thickness have been prepared via nonrepetitive, single-step deposition. In these studies, BaTiO 3 coatings were prepared from starting solutions of molar compositions, Ba(CH 3 COO) 2 : Ti(OC 3 H 7 i ) 4 :PVP:CH 3 COOH:H 2 O:i-C 3 H 7 OH ϭ 1:1:x:9.08:20:20, where x ranged from 0 -1.5.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Crack-free BaTiO 3 and PZT films Ͼ1 m in thickness have been prepared via nonrepetitive, single-step deposition. In these studies, BaTiO 3 coatings were prepared from starting solutions of molar compositions, Ba(CH 3 COO) 2 : Ti(OC 3 H 7 i ) 4 :PVP:CH 3 COOH:H 2 O:i-C 3 H 7 OH ϭ 1:1:x:9.08:20:20, where x ranged from 0 -1.5. The average molecular weight of PVP used was 6.3 ϫ 10 5 , and x was defined for the monomer (the polymerization repeating unit) of PVP.…”
Section: Introductionmentioning
confidence: 99%